Emotional responses to irony and emoticons in written language: evidence from EDA and facial EMG - Thompson, Dominic; Mackenzie, Ian G.; Leuthold, Hartmut; Filik, Ruth (Wiley, 2016)
While the basic nature of irony is saying one thing and communicating the opposite, it may also serve additional social and emotional functions, such as projecting humour or anger. Emoticons often accompany irony in computer-mediated communication, and have been suggested to increase enjoyment of communication. In the current study, we aimed to examine on-line emotional responses to ironic vs. literal comments, and the influence of emoticons on this process. Participants read stories with a final comment that was either ironic or literal, praising or critical, and with or without an emoticon. We used psychophysiological measures to capture immediate emotional responses: electrodermal activity to directly measure arousal, and facial electromyography to detect muscle movements indicative of emotional expressions. Results showed higher arousal, reduced frowning, and enhanced smiling for messages with rather than without an emoticon, suggesting that emoticons increase positive emotions. A tendency towards less negative responses (i.e., reduced frowning and enhanced smiling) for ironic than literal criticism, and less positive responses (i.e., enhanced frowning and reduced smiling) for ironic than literal praise suggests that irony weakens the emotional impact of a message. The present findings indicate the utility of a psychophysiological approach in studying on-line emotional responses to written language.